Kelayakan Lokasi untuk Pengembangan Budi Daya Karang Hias di Teluk Talengen Kabupaten Kepulauan Sangihe - Silalahi, Diany R.A; Ngangi, Edwin L.A; Undap, Suzanne L (e-Journal BUDIDAYA PERAIRAN, 2015)
A research had been conducted to study the condition of waters environment and water quality appropriate for the culture of ornamental coral at Talengen Bay and to analyze its financial feasibility. Â This research was conducted at Talengen Bay, Regency of Sangihe Archipelago through observation method.Â  Observation station representing the characteristic of Talengen Waters included at the center of the bay, at downstream, and behind the â€œteripangâ€ culture area.Â  Waters condition data were protection, bottom substrate, flow rate, depth, turbidity, pH, salinity, temperature, dissolve oxygen, nitrate, phosphate, and total suspended solid.Â  Financial feasibility data were obtained from secondary data and interview with respondents.Â  The data were analyze descriptively.Â  In general, water condition at Talengen Bay was suitable for the development of ornamental coral culture.Â  Flow rate at Talengen Bay was lower than standard criteria and thus required certain consideration. Financially the ornamental coral culture at Talengen Bay provided positive benefits.Â  Its total revenue achieved Rp. 193.582.000,00Â  and profit rate as much as 81.91%. Keywords :Â  Talengen Bay, ornamental coral, site feasibility, financial feasibility